2019
DOI: 10.1002/art.40905
|View full text |Cite
|
Sign up to set email alerts
|

Reducing or Maintaining the Dose of Subcutaneous Tocilizumab in Patients With Rheumatoid Arthritis in Clinical Remission: A Randomized, Open‐Label Trial

Abstract: Objective. To evaluate the efficacy and safety of increasing the dose interval of subcutaneous tocilizumab (TCZ-SC) in patients with rheumatoid arthritis (RA) who are in clinical remission.Methods. RA patients with active disease and an inadequate response to conventional synthetic disease-modifying antirheumatic drugs (csDMARDs) or to a biologic agent were entered into a single-arm treatment phase with 162 mg of TCZ-SC administered once weekly (TCZ-SC 162 mg qw) as monotherapy or in combination with a csDMARD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 37 publications
(54 reference statements)
0
7
0
1
Order By: Relevance
“…Patients with IR to DMARDs received TCZ 162 mg s.c. weekly for 24 weeks in the ToSpace open-label RCT and those achieving DAS28-ESR <2.6 (at week 20 and week 24) were randomised to continue TCZ 162 mg weekly or switch to TCZ 162 mg every 2 weeks for 24 weeks. Seventy-three per cent of patients switched to TCZ Q2W could maintain DAS28-ESR <2.6 at week 48 vs 90% continuing weekly TCZ treatment (p=0.004) 48…”
Section: Resultsmentioning
confidence: 99%
“…Patients with IR to DMARDs received TCZ 162 mg s.c. weekly for 24 weeks in the ToSpace open-label RCT and those achieving DAS28-ESR <2.6 (at week 20 and week 24) were randomised to continue TCZ 162 mg weekly or switch to TCZ 162 mg every 2 weeks for 24 weeks. Seventy-three per cent of patients switched to TCZ Q2W could maintain DAS28-ESR <2.6 at week 48 vs 90% continuing weekly TCZ treatment (p=0.004) 48…”
Section: Resultsmentioning
confidence: 99%
“… The majority of the evidence relates to anti-TNF therapy, although results for other mechanisms of action that have been studied appear similar, including rituximab (11), abatacept (12), tocilizumab (13) and baricitinib (trial studied the reduction of 4mg/day dose to the approved dose in Canada of 2 mg/day) (14).…”
Section: Rationale and Key Remarksmentioning
confidence: 99%
“…No studies were identified for patients with PsA or a mixed population of IA. Of the included trials, 64% were funded by the drug manufacture (29,30,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) with no difference between RA or axSpA (12/18 trials [67%] vs. 3/5 trials [60%], respectively). However, significantly more withdrawal studies (10/11 trials [91%]) were funded by the manufacture compared to tapering trials (8/16 trials [50%]).…”
Section: Study Characteristics and Risk Of Bias In Individual Trialsmentioning
confidence: 99%